Strategi Komunikasi Pemerintah Desa Pandean, Kabupaten Ngawi, dalam Membangun E-Government melalui Website Desa yang Efektif - Eko Wahyu Saputro; Hasbullah Azis; Rahmat Wisudawanto (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Currently, digital technology has transformed how governments operate and interact with their citizens. This development has brought significant changes to governance, especially at the village level. With the advancement of technology, village governments now have the opportunity to be more transparent, efficient, and responsive to the needs of their citizens. One of the efforts made is the utilization of village websites as a tool to build e-government, which facilitates access to information and services for the public. This study aims to analyze the communication strategy of the Government of Pandean Village, Ngawi Regency, in building e-government through the use of the village website. Using a communication strategy approach that includes audience analysis, message development, method determination, and media selection, this research seeks to provide an understanding of how the village government optimizes the use of technology to improve interactions with the community. The study adopts a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. The results of the study show that the communication strategy of the Government of Pandean Village has been well implemented in two main aspects: audience analysis and message development. The village government has identified the information needs of its citizens and tailored the messages conveyed through the village website. However, the research also revealed shortcomings in the methods of delivery and media development, particularly in optimizing interactive features that could encourage public participation. Additionally, there is a need for increased use of social media and two-way communication features on the village website to strengthen public engagement in the development process and decision-making. Overall, while there has been progress in implementing e-government, there are still several aspects that need improvement to enhance the effectiveness of communication between the village government and the community.